Measurement precision enhancement of surface plasmon resonance based angular scanning detection using deep learning - Kitsada Thadson; Suvicha Sasivimolkul; Phitsini Suvarnaphaet; Sarinporn Visitsattapongse; Suejit Pechprasarn (Scientific Reports, 2022)
RIU for 2-dimensional contour fitting using Horner's method.
Keywords: Plasmonic and Surface Plasmon Research; Advanced Biosensing Techniques and Applications; Biosensors and Analytical Detection